Prevalence of HIV/AIDS in antenatal patients in a tertiary health care center - Oberoi, Harleen; Kaur, Kiranjeet; Kaur, Amrit Pal (International Journal of Research in Medical Sciences, 2025)
Background: India is way behind in its battle against HIV-AIDS. Human immunodeficiency virus is spreading at an alarming rate; statistics show that India has the third largest number of people living with the virus. According to National AIDS control organisation (NACO), the overall prevalence is 0.29% among the ANC clinic patients in India. HIV still has a stigma in this country, thus exact data and appropriate studies are not available to take relevant steps. Methods: After taking written consent and explaining the protocols, 5-ml of blood samples are collected in Clot vials and tested for HIV virus by ELISA. Positive samples were again sent to the ICTC center for further testing. The "opt-out" approach to HIV testing is offered to all women as part of routine antenatal tests. Women who are tested positive are also tested for HBV and HCV by ELISA. Results: Out of 40054 ANC patients tested in the last 5 years, 42 were tested positive for HIV which accounts for 0.12%. The coinfection rate of HBV and HCV was 0.007% and 0.017%. They were further classified based on specific criteria including age, education status, gravida, trimester in which they were detected and if they belonged to rural/urban household and co-infection with HCV and HBV. Conclusions: HIV-AIDS a disease with less mortality but major morbidity if not controlled well with timely ART. Appropriate management must be instituted to reduce the consequences of HIV in pregnancy with preconception counselling and planning pregnancies when the viral load is minimum.